Trade policy and income inequality: New evidence - Savvides, Andreas (My University, 1998)
This paper uses recently available data to investigate the link between income inequality and trade protection. It finds that among less developed countries, more open economies experienced increased income inequality during the late 1980s. Trade policy has had no effect on income inequality in developed countries.
Keywords: F13; Income distribution; O15; Trade policy